Framework for Cloud Based Document Management System with Institutional Schema of Database - Bani Ahmad, Ahmad Y. A.; Kumari, D. Karuna; Shukla, Aasheesh; Deepak, A.; Chandnani, Maulik; Pundir, Sumit; Shrivastava, Anurag (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The majority of applications will probably continue to use relational database management systems as their preferred technology. RDBMS providers have created cutting-edge strategies to quicken the installation procedure. For good reason, relational databases have long served as the foundation of databases for a number of products. Using relational databases has a number of benefits. The market share maintained by relational database management systems is under threat from NoSQL database technologies. There are many distinct types of NoSQL databases, and they were all created specifically to do certain tasks that RDBMSs were not designed to carry out. The many database structure options accessible to them have given a renewed sense of independence to many different kinds of organizations. Despite their recent successes and their capacity to manage enormous volumes of data, NoSQL databases are not the best option for all plans, and they are not likely to unseat relational software from its position as the industry standard database any time soon. Despite their recent achievements and proficiency in handling enormous volumes of data. Depending on the goals your company has set for itself, conventional databases, NoSQL databases, or a combination of the two may be able to give the most information to your organization. Cloud database services may leverage cloud computing to achieve the objectives of ideal scalability, high accessibility, multi-tenancy, and real resource supply. But organizing these databases in a cloud computing environment is difficult since they need ACID (Atomicity, Consistency, Isolation, and Durability) exclusivity. The goal of this study is to look at the state-of-the-art regarding the need for cloud databases and the various frameworks available. In order to approach the services that are described by the cloud computing system, it defines the typical operations that are conducted on a cloud database by a cloud computing proposal.